A sharing session by a visiting research fellow of the Oxford Centre for clinical magnetic resonance research (OCMR) / Shubashini Gnanasan - Gnanasan, Shubashini (Faculty of Pharmacy, 2024)
Dr. Shubashini Gnanasan, a senior lecturer from the Faculty of Pharmacy, UiTM presented her research experience of being part of a clinical trial team at the University of Oxford. She has been conducting ethnography to understand the facilitators and the challenges of running a clinical trial under the supervision of Professor Masliza Mahmod from University of Oxford. She provides individualised pharmaceutical care to participants in the ‘Followup, Open-Label, Research Evaluation of Sustained Treatment with Aficamten in Hypertrophic Cardiomyopathy (FOREST-HCM)’.